Effect of heat treatment on microstructures and properties of Zr-rich α TiZrAl alloy - FU Xiaoyun; WU Baolin; XU Zaidong; WAN Gang; LI Zhou; LI Jianbo (Cailiao gongcheng, 2024)
The microstructures and properties of two kinds of zirconium-enriched α alloys （Ti60Zr40）97Al3（mass fraction/%，the same below） and （Ti50Zr50）97Al3 via different heat treatments were investigated and analyzed based on optical microscope （OM） observation， differential scanning calorimetric （DSC） measurement， X-ray diffraction （XRD） measurement， scanning electron microscope （SEM） observation and tensile tests at room temperature.The results show that after 850 ℃/40 min annealing， microstructures consisting of basket-weave α phase and a small amount of reticular β phase are formed in the alloys. After 850 ℃/40 min quenching， the acicular α' martensite phase is formed. After 850 ℃/40 min quenching and then 600 ℃/4 h aging， a large part of α' martensite phase converts into α phase， and the microstructures of the alloys consist of α and α'remain phases. The yield strength of the T40Z3A alloy can reach 1100 MPa， with a favourable tensile elongation of 7%. The T50Z3A alloy exhibits higher strength but lower ductility than those of the T50Z3A alloy. Due to the higher content of Zr element， the T50Z3A alloy has more reticular β phase after annealing and more remaining α' martensite phase after quenching and aging， which results in higher strength and lower ductility.